Telaah Usabilitas Aplikasi Pendidikan Agama Islam SIPRAKTISPULSA di SD Negeri 1 Pule - Rama Praditya, Dendy; Huda Rohmadi, Syamsul (Ikatan Da'i Indonesia, 2025)
Islamic Religious Education plays a crucial role in shaping the character and morals of every Muslim individual. In this era of rapid technological advancement, the development of learning methods in education will also evolve, including in the field of Islamic Religious Education. Therefore, SDN 1 Pule created the sipraktispulsa application. The purpose of this study was to examine the application's usability. This study used a descriptive qualitative approach. Data collection included interviews with Islamic Religious Education teachers and sixth-grade students, classroom observations, and document analysis. The results of this study concluded that this application contains five usability criteria: learnability, efficiency, memorability, and errors/satisfaction.